2018
DOI: 10.5812/ijp.80180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Complementary Medicine on Successful Breastfeeding and its Associated Issues in the Postpartum Period

Abstract: Context: Breastfeeding initiation is an important event during the postpartum period. Despite the significance of exclusive breastfeeding in infant health, some common breast issues lead to the early cessation of breastfeeding. Therefore, various complementary medicine techniques are used to increase the length and quality of breastfeeding. Objectives: The current review study collected evidence on the impacts of complementary medicine on successful breastfeeding and breastfeeding-associated problems in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…This study was reported based on the PRISMA guidelines [ 37 ]. The systematic search in the databases identified 155 articles.…”
Section: Methodsmentioning
confidence: 99%
“…This study was reported based on the PRISMA guidelines [ 37 ]. The systematic search in the databases identified 155 articles.…”
Section: Methodsmentioning
confidence: 99%
“…Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statements were used to assess the quality of the studies. The STROBE statement as a valid tool consists of a checklist of 22 items to assess the quality of different parts of the observational studies [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Out of a total of 17 related studies, 3 [ 22 , 25 , 26 ] had a cross-sectional design, 1 [ 24 ] had a case-control design, 2 [ 27 , 28 ] had a semi-experimental design, and 11 [ 19 , 29 – 38 ] were randomized controlled trials. Furthermore, 10 studies [ 19 , 22 , 25 , 28 , 29 , 32 , 33 , 35 – 37 ] were performed in Iran, 3 [ 18 , 27 , 30 ] in Turkey, and 1 [ 26 ] in Jordan, 1 [ 31 ] in India, 1 [ 35 ] in Italy, and 1 [ 31 ] in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…The STROBE statement, as an authoritative tool, consists of a 22-item checklist. The checklist items concentrate on reporting or evaluating different sections of observational studies [ 23 , 24 ]. The STROBE checklist consists of 6 general sections under the following headings: title and abstract, introduction, methods, results, discussion, and other information.…”
Section: Criteria For Considering Studies For This Reviewmentioning
confidence: 99%